Digital Divide in Education in North Maluku: The Technology Gap between Cities and Villages - Adiyana Adam; Sahrul Takim; Rustam Tidore; Agus, Agus; Nurmala Buamona; Khader Rajabi (Tinta Emas Institute, 2025)
This document discusses the digital divide in education in North Maluku, which poses a significant challenge to the quality of education, especially between urban and rural areas. Despite efforts to improve access to technology through the provision of satellite internet and other initiatives, challenges such as limited infrastructure, high operational costs, and lack of digital literacy continue to hamper progress. The proposed policy recommendations include the development of integrated technology infrastructure, the establishment of training centers, the allocation of special funds for remote areas, cooperation with the private sector, and the development of monitoring and evaluation systems. With the implementation of appropriate policies and commitment from all stakeholders, it is hoped that the digital divide can be minimized, creating equality in the quality of education, and increasing the potential of students in North Maluku.